Nordic Bioeconomy Pathways: Future narratives for assessment of water-related ecosystem services in agricultural and forest management - Rakovic, Jelena; Futter, Martyn N.; Kyllmar, Katarina; Rankinen, Katri; Stutter, Marc I.; Vermaat, Jan; Collentine, Dennis (Ambio, 2020)
Further development of the bioeconomy, the substitution of bioresources for fossil resources, will lead to an increased pressure on land and water resources in both agriculture and forestry. It is important to study whether resultant changes in land management may in turn lead to impairment of water services. This paper describes the Nordic Bioeconomy Pathways (NBPs), a set of regional sectoral storylines nested within the global Shared Socioeconomic Pathways (SSP) framework developed to provide the BIOWATER research program with land management scenarios for projecting future developments to explore possible conflicts between land management changes and the Water Framework Directive (WFD). The NBPs are a set of narrative storylines capturing a range of plausible future trajectories for the Nordic bioeconomy until 2050 and that are fit for use within hydrological catchment modelling, ecosystem service studies and stakeholder dialogue about possible changes in agricultural and forestry management practices.